2015
DOI: 10.1007/s40726-015-0017-x
|View full text |Cite
|
Sign up to set email alerts
|

Application of Stabilized Nanoparticles for In Situ Remediation of Metal-Contaminated Soil and Groundwater: a Critical Review

Abstract: Remediation of soil and groundwater contaminated with toxic metals has been a major environmental challenge for decades. Yet, cost-effective and sustainable in situ remediation technologies remain lacking. Over the last 15 years or so, an innovative in situ remediation strategy has shown promising by means of stabilized nanoparticles. Stabilized nanoparticles are prepared using novel stabilizers that facilitate the deliverability and transport of nanoparticles in the subsurface. This study reviews synthesis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(21 citation statements)
references
References 99 publications
1
20
0
Order By: Relevance
“…The earliest summary of synthesis, characterization, reactivity and in situ field tests for non-stabilized nZVI (Zhang, 2003(Zhang, ) 2006 Morphology, reactivity and mobility of nZVI. Comparison of in situ and ex situ application of nZVI Johnson, 2006) 2006 Materials and engineering aspects of non-stabilized nZVI (Li et al, 2006(Li et al, ) 2010 Effects of organic coating on reactivity of ZVI or nZVI (Tratnyek et al, 2011(Tratnyek et al, ) 2012 Perspectives on nZVI injection strategy Scott, 2012) 2013 Updated account of developments and field experiences of nZVI (Yan et al, 2013(Yan et al, ) 2014 Use of ZVI or nZVI for groundwater remediation and wastewater treatment (Fu et al, 2014(Fu et al, ) 2014 Use of nZVI for groundwater remediation (Tosco et al, 2014(Tosco et al, ) 2015 Limitations and recent developments of ZVI and nZVI (Guan et al, 2015(Guan et al, ) 2015 Use of stabilized nanomaterials for metal contaminants in soil/groundwater (Liu et al, 2015(Liu et al, ) 2016 Interactions between macromolecular coatings and nanomaterials (Louie et al, 2016) Compared with bare nZVI. The stabilization enhanced transport, but the stabilized nZVI decreased TCE dechlorination rate by a factor of 4.…”
Section: Publication Date Focus Area Reference 2003mentioning
confidence: 99%
See 1 more Smart Citation
“…The earliest summary of synthesis, characterization, reactivity and in situ field tests for non-stabilized nZVI (Zhang, 2003(Zhang, ) 2006 Morphology, reactivity and mobility of nZVI. Comparison of in situ and ex situ application of nZVI Johnson, 2006) 2006 Materials and engineering aspects of non-stabilized nZVI (Li et al, 2006(Li et al, ) 2010 Effects of organic coating on reactivity of ZVI or nZVI (Tratnyek et al, 2011(Tratnyek et al, ) 2012 Perspectives on nZVI injection strategy Scott, 2012) 2013 Updated account of developments and field experiences of nZVI (Yan et al, 2013(Yan et al, ) 2014 Use of ZVI or nZVI for groundwater remediation and wastewater treatment (Fu et al, 2014(Fu et al, ) 2014 Use of nZVI for groundwater remediation (Tosco et al, 2014(Tosco et al, ) 2015 Limitations and recent developments of ZVI and nZVI (Guan et al, 2015(Guan et al, ) 2015 Use of stabilized nanomaterials for metal contaminants in soil/groundwater (Liu et al, 2015(Liu et al, ) 2016 Interactions between macromolecular coatings and nanomaterials (Louie et al, 2016) Compared with bare nZVI. The stabilization enhanced transport, but the stabilized nZVI decreased TCE dechlorination rate by a factor of 4.…”
Section: Publication Date Focus Area Reference 2003mentioning
confidence: 99%
“…Laboratory and field studies have demonstrated that stabilized nZVI particles can effectively degrade halogenated organics, and immobilize toxic metals, metalloids and radionuclides (He and Zhao, 2005He et al, , 2009aHe et al, , 2009bHe et al, , 2010Liu et al, 2015;Xu and Zhao, 2007). However, because of the complexity of the soil physical and biogeochemical properties, the effectiveness and feasibility of the in situ remediation technology using stabilized nZVI are yet to be further studied, especially at the field scale (Liu et al, 2015). The technology constraints and environmental factors that affect the particle reactivity, mobility and environmental fate are yet to be determined or confirmed under field conditions.…”
Section: Introductionmentioning
confidence: 99%
“…2,5,10,15,20,40,60,80, or 100 mg/L -ZnSO4 = 1, 1. 5, 3, 6, 8, 10, 15, 20, 25, 30, 40, 50, 64, or heavy metals such as lead and cadmium [12] , and organic compounds such as polyaromatic hydrocarbons [13] . Significant uptake by MENPs has been seen in systems saturated with a contaminant (see Table 4) [14], [15], [16], [17], [18], [19] .…”
Section: Risks Of Nanoparticlesmentioning
confidence: 99%
“…However, this technique is relatively much expensive. The nano-particles with NZVI can be desorbed in the presence of phosphorus present in the ground water or by addition of phosphate into groundwater and reused [34][35][36][37] .…”
Section: Fig 1: Arsenocosis Patientmentioning
confidence: 99%